Dimensionamento, emissões de gases de efeito estufa e payback ambiental de um sistema de energia solar fotovoltaico - Schultz, Herwin Saito (2021)
Traditionally, electricity generation systems use fossil fuels in their production process and emit a large amount of greenhouse gases. To reduce these emissions, ways of obtaining energy that are less aggressive to the environment should be sought. In this context, the use of renewable sources acquires importance in the energy matrix. Photovoltaic solar systems generation can represent less polluting energy source and can replace non-renewable sources powered by fossil fuels, as is the case of natural gas thermoelectric power plants. The state of Paraíba has great potential for solar energy generation, having one of the highest solar irradiation rates in the country. The general objective of this study was designing a 16.4 MW photovoltaic solar system located in the hinterland of Paraíba and quantifying the associated greenhouse gases emissions with its environmental payback. The solar system was designed to minimize the Leveled Energy Cost. greenhouse gases emissions were quantified through Life Cycle Assessment, expressing the environmental impact in terms of energy generated (kg of CO2-eq / kWh) and adopting the procedures presented by ISO 14040 and 14044. For life cycle assessment, the SimaPro v.9.1.0.8 software, the Ecoinvent 3.5 database and the IPCC 2013 GWP 100a method were used for a life cycle assessment from cradle to grave. The determination of the environmental payback was in relation to the Brazilian electric mix of 2019 and also took into account the degradation of the panels in the energy production. As a result, a solar system capable of supplying 521,443 MWh in 25 years was obtained, with an emission factor of 0.044 kg of CO2-eq / kWh, an environmental payback of 5 years and 8 months and an emission factor at least 10 times lower in comparison, with the natural gas thermoelectric power plants. Solar panels are the main contributors to greenhouse gases emissions, representing 90.59% of the total. It is concluded that photovoltaic solar systems have great importance in the search for reductions in greenhouse gases emissions and even in a country that has a predominantly renewable electrical matrix, its application is still advantageous.